Paratriathletes' physiological and thermoregulatory response to training load and competition - Stephenson, B. T. (University Loughborough, 2019)
Paratriathlon is a multi-impairment, endurance sport which made its Paralympic Games debut in 2016. Athletes` impairments typically include but, are not limited to, spinal cord injury; cerebral palsy, or other neurological disorders; amputations or visual impairments. However, despite athletes displaying impairments that present several considerations for coaches and practitioners, there has been very little research in the sport. Specifically, there is little understanding of how athletes` impairments may impact their physiological response to acute or chronic changes in training load. Similarly, it is not known how consequences of athletes` impairments affect thermoregulation and the ability to adapt to the heat. Thus, this thesis aimed to elucidate these unknown areas whilst bridging the knowledge gap to research in able-bodied triathlon. The first two studies of this thesis investigated paratriathletes` response to changes in training load, longitudinally (Chapter four) and more acutely (Chapter five)